MANTRA PELARIS DAGANGAN DALAM MASYARAKAT HILIA PARIK NAGARI LUBUK BASUNG KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Metty Jasentika; Hamidin Hamidin; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this article is to structure the text mantra pelaris dagangan, the supporting aspects of reading mantra pelaris dagangan, and the process of inheritance mantra pelaris dagangan. The data were collected by observation and taking a note the data. The techniques used are recording techniques and dikte technique, because some people say if the mantra is recorded, it will reduce the benefit of mantra itself. The research finding is the text structure mantra pelaris dagangan, the supporting aspects of reading mantra pelaris dagangan, and the process of inheritance mantra pelaris dagangan.